HICK'S PLURALISM AND RUMI'S MATHNAWI: THE CONTINUED PROPAGATION OF MISAPPROPRIATED LINES - Al-Aidrus, Mohamed Ajmal Abdul Razak (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
HICK'S PLURALISM AND RUMI'S MATHNAWI: THE CONTINUED PROPAGATION OF MISAPPROPRIATED LINES